Clustering History Data Penjualan Menggunakan Algoritma K-Means - Dharma Putra, Yogiswara; Sudarma, Made; Swamardika, Ida Bagus Alit (Majalah Ilmiah Teknologi Elektro, 2021)
The company has a desire to develop an increase in its business so that it is not eroded by the very tight business competition. PT. Baliyoni Saguna is a company engaged in information technology and telecommunications which currently helps its customers to provide the best solutions according to customer needs. Product quality is a major factor in keeping customers alive and satisfied with the products provided by PT. Baliyoni Saguna. These products need to be reviewed in order to have a reference in creating the best products. Clustering is a method that can be used to see the level of sales that have been made based on the formed clusters. The K-Means algorithm is a method capable of processing sales history data owned by PT. Baliyoni Saguna in forming groups according to the item category of the item. The K-Means algorithm is able to provide convenience in processing large data so that it can be processed more quickly and efficiently. The results of the application of the K-Means algorithm formed 3 clusters representing the most desirable, least desirable, and least desirable categories. In the most desirable category there are 5 total items, 4 in the interested category there are 4 total items, and 14 items less desirable. These results are expected to help in creating quality goods so as to maintain product quality and customer satisfaction.   Keywords – Clustering, K-Means Algorithm, PT. Baliyoni Saguna